The effect of using different-level stations and various motor exercises on some basic skills and physical and motor abilities of five-a-side soccer. (Journal of the College of Basic Education, 2022)
The research included five chapters as follows:The teaching methods used by the teacher are considered one of the most important aspects of the educational process, and each method has a specific role in preparing the learners in terms of knowledge, skill, physical and emotional. The teacher's reliance on one method of learning does not necessarily lead to all learners learning at the same level, and from here the teacher must use many learning methods in order to provide a variety of educational situations suitable for the largest number of learners.